Strategic Business Development Through Product Differentiation: Case Study PT Galang Prakarsa Sodara (GPS) - Pulunggono, Ahmad Heko; Harianto, Harianto; Asnawi, Yudha Heryawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to improve PT GPS’s business strategy by (1) examining the internal strengths and weaknesses, and external opportunities and threats; (2) formulating alternative strategies using SWOT; and (3) prioritizing strategies with the Advanced SWOT (A’WOT) method. Primary data were collected from nine purposively selected experts via interviews, questionnaires, and field observations. Secondary data came from company records, government publications, and industry reports. Analyses used VRIO and Porter’s Five Forces, followed by IFE and EFE matrices. The SWOT matrix generated strategies, and A’WOT determined priorities. The IFE-EFE placed PT GPS in Quadrant II (grow and build) of the IE matrix. Nine strategies emerged, with the top four priorities: (1) optimizing product quality and variety (ST1), (2) expanding market penetration via distribution optimization (SO1), (3) developing innovative product variations for new segments (SO2), and (4) enhancing monitoring and branding in distribution channels (WO1). PT GPS’s competitive position can be strengthened by focusing on product differentiation, expanding distribution reach, and continuous innovation. Improving branding and product monitoring will reinforce market presence and customer loyalty. Implementing these strategies in sequence will enable sustainable growth and resilience against competitive pressures in the meatball industry. This research enriches MSME strategy literature by integrating VRIO, Porter’s Five Forces, SWOT, and A’WOT for objective strategy prioritization in processed food markets. Keywords: A’WOT, meatball, positioning, product differentiation, SWOT.